A Toda Lattice in Dimension 2 and Nevanlinna Theory - Eremenko, A. (Журнал математической физики, анализа, геометрии, 2007)
It is shown how to study the 2-D Toda system for SU(n+1) using Nevanlinna theory of meromorphic functions and holomorphic curves. The results generalize recent results of Jost Wang and Chen-Li.